Axial Compression Performance and Ultrasonic Testing of Multicavity Concrete-Filled Steel Tube Shear Wall under Axial Load - Hongbo Li; Pengfei Yan; Hao Sun; Jianguang Yin (Advances in Civil Engineering)
In this study, the mechanical performance of multicavity concrete-filled steel tube (CFST) shear wall under axial compressive loading is investigated through experimental, numerical, and theoretical methodologies. Further, ultrasonic testing is used to assess the accumulated damage in the core concrete. Two specimens are designed for axial compression test to study the effect of concrete strength and steel ratio on the mechanical behavior of multicavity CFST shear wall. Furthermore, a three-dimensional (3D) finite element model is established for parametric studies to probe into compound effect between multicavity steel tube and core concrete. Based on finite element simulation and limit equilibrium theory, a practical formula is proposed for calculating the axial compressive bearing capacity of the multicavity CFST shear wall, and the corresponding calculation results are found to be in good agreement with the experimental results. This indicates that the proposed formula can serve as a useful reference for engineering applications. In addition, the ultrasonic testing results revealed that the damage process of core concrete under axial load can be divided into three stages: extension of initial cracks (elastic stage), compaction due to hooping effect (elastic-plastic stage), and overall failure of the concrete (failure stage).